RETRACTED: Post COVID green intellectual capital management with the mediation of organizational learning capability - Schislyaeva, Elena Rostislavovna; Krasovskaya, Inna Petrovna; Plis, Kristina Sergeevna (Frontiers in Energy Research, 2022)
This study aims to investigate the features of managing intellectual capital regarding the influence on firm performance in the Russian banking sector after COVID-19. The study considered general importance of intellectual capital firm’s bundle of all knowledge assets that can be utilized for different strategic moves. The research used primary data collected from managers in the Russian financial sector using a structured questionnaire from 364 respondents. The intellectual capital aspects used were human, relational, and structural capital. Organizational learning capability was a mediator, while firm performance was the independent variable. The hypotheses were evaluated using Structural Equation Modeling. The study results indicated that relational and human capital have a positive and significant influence on firm performance, but not structural capital. Relational capital, structural capital, and human capital were found to positively and significantly influence firm performance. Organizational learning capability was found to have a positive and significant effect on firm performance and a mediator of the impact of intellectual capital on firm performance. The study recommends that managers in the banking sector enhance their relations and interactions with customers, suppliers, and trade partners.